Face the music [compact disc, unabridged] : a life exposed - Stanley, Paul, 1952- (Harper Audio, 2014)
Paul Stanley mixes personal revelations and gripping, gritty war stories about the highs and lows of life inside and beyond KISS. He takes us back to his childhood in the 1950s and '60s, a traumatic time made more painful thanks to a physical deformity. Born with microtia, he grew up partially deaf, with only one ear; a visual difference that set him apart in a socially conformist age. Yet it instilled in him the burning drive to succeed in the most unlikely of pursuits: music.